SELF ADAPTIVE SOFTWARE DENGAN TEKNIK CASE-BASED REASONING UNTUK MENINGKATKAN PERFORMA APPLICATION SERVER - Muhamad Nur; Domo Pranowo Kuswandono (Sekolah Tinggi Teknik - PLN, 2018)
Performance of application server is an important attribute that must be maintained quality and stability, because application server operated in dynamic environment with fluctuating user loads and resource levels, its potentially caused unpredictable errors. In order application server performance still optimal, it is need maintains configuration application parameters. But, do that process need deep observation each environment condition changed and of course the cost and time. The approach that can be used is self-adaptive (autonomic computing). Self-adaptive can configure application parameters automatically. Best combination application parameters configuration can be stored on a repository and used as reference when decide new decision for configuration of application server parameters when similar condition is occurred. Cased-based reasoning can do the process. Best approach will be used is self-adaptive with case-based reasoning. This research implements the approach on an experiment application that deployed on glassfish application server. The results show that self-adaptive with case-based reasoning can improve application server performance with significant improvement.